2023
DOI: 10.3390/ma16062178
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Dehydrogenation Properties of LiAlH4 by Addition of TiSiO4

Abstract: Given its significant gravimetric hydrogen capacity advantage, lithium alanate (LiAlH4) is regarded as a suitable material for solid-state hydrogen storage. Nevertheless, its outrageous decomposition temperature and slow sorption kinetics hinder its application as a solid-state hydrogen storage material. This research’s objective is to investigate how the addition of titanium silicate (TiSiO4) altered the dehydrogenation behavior of LiAlH4. The LiAlH4–10 wt% TiSiO4 composite dehydrogenation temperatures were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…Two regions of Al–H modes were discovered (i) [AlH 4 ] − bending at 800−900 cm −1 and (ii) [AlH 4 ] − stretching at 1600−1800 cm −1 . A similar study was disclosed by Yusnizam et al [ 55 ] which observed that a new peak at 1403 cm −1 was detected which shows that the addition of TiSiO 4 could weak the Al–H bond of LiAlH 4 .
Fig.
…”
Section: Resultssupporting
confidence: 80%
“…Two regions of Al–H modes were discovered (i) [AlH 4 ] − bending at 800−900 cm −1 and (ii) [AlH 4 ] − stretching at 1600−1800 cm −1 . A similar study was disclosed by Yusnizam et al [ 55 ] which observed that a new peak at 1403 cm −1 was detected which shows that the addition of TiSiO 4 could weak the Al–H bond of LiAlH 4 .
Fig.
…”
Section: Resultssupporting
confidence: 80%